Combining high carotenoid, grain protein content and rust resistance in wheat for food and nutritional security - Padhy, Asish Kumar; Sharma, Achla; Sharma, Himanshu; Srivastava, Puja; Singh, Satinder; Kaur, Parampreet; Kaur, Jaspal; Kaur, Satinder; Chhuneja, Parveen; Bains, Navtej Singh (Frontiers in Genetics, 2023)
Globally, malnutrition has given birth to an alarming predicament, especially in developing countries, and has extensively shifted consumer preferences from conventional high-energy diets to a nutritionally balanced, cost-effective, sustainable, and healthy lifestyle. In keeping with this view and the mandate for developing high-yielding, disease-resistant biofortified staple food (wheat) for catering to the demand-driven market, the current research aimed at stacking together the enhanced grain protein content, carotenoid content, and disease resistance in an elite bread wheat background. The Y gene (PsyE1) and the GpcB1 gene were used as novel sources for enhancing the grain carotenoid and protein content in the commercial elite bread wheat cultivar HD2967. The combination also led to the stacking of resistance against all three foliar rusts owing to linked resistance genes. A stepwise hybridization using Parent 1 (HD2967 + PsyE1/Lr19/Sr25) with Parent 2 (PBW550 + GpcB1/Yr36+ Yr15), coupled with a phenotypic-biochemical selection, narrowed down 2748 F2 individuals to a subset of 649 F2 plants for molecular screening. The gene-specific markers PsyE1, PsyD1, Xucw108, and Xbarc8 for the genes PsyE1, PsyD1, GpcB1, and Yr15, respectively, were employed for forward selection. Four bread wheat lines positive for all the desired genes with high carotenoid (>8ppm) and protein (>13%) content were raised to the F5 generation and will be evaluated for yield potential after bulking. These improved advanced breeding lines developed following multipronged efforts should prove a valuable and unique source for the development of cultivars with improved nutritional quality and rust resistance in wheat breeding programs.